Understanding and improving communication processes in an increasingly multicultural aged care workforce - Nichols, Pam; Horner, B.; Fyfe, K. (Elsevier Ltd, 2015)
This study explored how culture shapes relationships in aged care and the extent to which the residential aged care sector supports a cohesive multicultural workforce. An exploratory methodology utilising semi-structured questionnaires collected data from 58 participants comprising: staff who provide direct care to residents; managers; and family members from six residential care facilities in Perth, Western Australia. Communication issues emerged as an over-arching theme, and included interpersonal communication, the effect of cultural norms on communication and the impact of informal and formal workplace policies relating to spoken and written language. Sixty percent of participants from a culturally and linguistically diverse (CaLD) background had experienced negative reactions from residents with dementia, linked to visible cultural difference. They used a range of coping strategies including ignoring, resilience and avoidance in such situations. CaLD participants also reported prejudicial treatment from non-CaLD staff. The findings highlight the need for organisations to incorporate explicit processes which address the multiple layers of influence on cross cultural communication: internalised beliefs and values; moderating effects of education, experience and social circumstance; and factors external to the individuals, including workplace culture and the broader political economy, to develop a cohesive multicultural workplace.